Clinical Hirsutism Secondary to Ovarian Clear Cell Carcinoma: A Rare Case Report - Muknisa, Liza; Nainggolan, Sarah Ika Nainggolan; Rusnaidi, Rusnaidi; Septivera, Yusra (Journal of Society Medicine, 2025)
Introduction: Hirsutism affects 5–15% of premenopausal women, predominantly due to hyperandrogenemia (80–90% of cases), with the remainder classified as idiopathic or normoandrogenic. While virilizing ovarian tumors are known causes, the association between hirsutism and ovarian clear cell carcinoma (OCCC) has not been previously documented. Case Description: A 51-year-old multiparous woman presented with progressive abdominal distension over one year and new-onset hirsutism (Ferriman–Gallwey score 13) involving the face, axillae, pubic area, and lower limbs. She reported abdominal pain, nausea, vomiting, anorexia, 5-kg weight loss, vaginal discharge, regular menses, and poorly controlled type 2 diabetes. Examination revealed an underweight habitus and a firm, irregular, mobile, tender pelvic-abdominal mass extending above the umbilicus. Laboratory evaluation showed hypoalbuminemia (3.22 g/dL), elevated creatinine (1.64 mg/dL), markedly raised CA-125 (1,480 U/mL), and normal serum testosterone (7.5 ng/dL). Imaging confirmed a 9.5 × 8.3 × 5.5 cm solid-cystic right ovarian mass with ascites and suspected peritoneal metastases. Total abdominal hysterectomy with surgical staging was performed; histopathology confirmed OCCC. Conclusion: This is the first reported case of clinical hirsutism in OCCC with normal testosterone levels, supporting a diagnosis of idiopathic hirsutism. Potential mechanisms include increased peripheral 5α-reductase activity, androgen receptor hypersensitivity, or local androgen production, warranting further molecular investigation.